Views and experiences of community pharmacists and superintendent pharmacists regarding the New Medicine Service in England prior to implementation - Wells, Katharine M.; Thornley, Tracey; Boyd, Matthew J.; Boardman, Helen F. (Elsevier, 2014)
Background: The New Medicine Service (NMS) was introduced to community pharmacies in England in October 2011. The NMS aims to improve adherence to new medicines in patients with selected long term conditions. The service consists of two follow-up consultations within 1 month in addition to usual care. Objectives: This study explored community pharmacist and superintendent pharmacist views and experiences of the NMS in the 5 weeks prior to its implementation to identify potential facilitators and barriers to its success. The study also investigated participant experiences of the introduction and provision of existing pharmacy services in order to contrast with the implementation of the NMS. Methods: This study consisted of four focus groups with a total of 15 community pharmacists representing locums and employees of small, medium and large chain pharmacies. In addition, 5 semi-structured interviews were conducted with superintendent pharmacists representing independent, small chain, supermarket and large multiple pharmacies. Data were audio-recorded, transcribed verbatim and thematically analyzed. Results: Both pharmacists and superintendent pharmacists were positive about the NMS and identified potential benefits for patients and the pharmacy profession. Awareness of the service was high, however, some confusion between the NMS and changes to Medicine Use Reviews was evident in all focus groups due to their similarity and coincidental implementation. This confusion was not observed in the interviews with superintendent pharmacists. Participants identified pharmacists' positive attitude, the similarity to current practice and the self-accreditation procedure as potential facilitators to service implementation. Potential barriers identified included a perceived lack of interest and awareness by GPs of the service, and the payment structure. Participants were concerned about the speed of implementation, and the absence of some materials needed prior to the start of the service. Conclusions: Participants were enthusiastic about the potential of the NMS to benefit patients and the pharmacy profession. Participants were able to identify several potential barriers and facilitators to the provision of the service. It remains to be seen whether the factors identified affected the early implementation of the service.